Pengembangan Profesionalisme Guru Melalui Pelatihan Penulisan Karya Tulis Ilmiah Pada MGMP Bahasa Inggris SMA Kabupaten Lombok Timur - Lalu Thohir; Ahmad Zamzam; Muhammad Amin (Jurnal Gema Ngabdi, 2019)
PTeacher professionalism development in teaching career requires documents dealing with scientific writing published in a journal. It was found that the article published by the English teachers in East Lombok district was still small in number and one of the factors causing this was the teachers’ lack of knowledge and skill in writing. Considering this problem, there needs to be of any assistance for the teachers in coping with their writing problems. This civil service program was to assist and develop the teachers’ competence in writing a journal article. Lectures, discussions, and group work were employed within the program taking place in Senior High School 2 Aikmel East Lombok and there were 25 teachers participating in this program. The participants, particularly the head of Senior High School English Teacher Association, greatly appreciated this program as it was really helpful to develop their writing competence and their motivation to write. The excessive teaching duty was another problem causing their lack of time to write a journal article and to develop their writing competence as well. The participants were in the hope that there will be follow-up activities or program dealing with action research, writing research findings and research finding dissemination process or publication